GIANT TEMPEH FESTIVAL: BETWEEN SUBJECT AND GIVEN SUBJECT (A STUDY OF GIANT TEMPEH FESTIVAL IN TLOGOREJO DISTRICT BUMIAJI VILLAGE BATU CITY IN SLAVOJ ZIZEK PERSPECTIVE ABOUT SUBJECT IDENTITY) - Muhammad Hayat (Jurnal Partisipatoris, 2019)
This research entitled Giant Tempeh Festival: Between subject and given subject was done in Tlogorejo district Bumiaji village, Batu City. "Subject" or term "subject awareness" means Tlogorejo Society grow and develop in their awareness of the power of values which they have produced so far. Meanwhile, term "given subject" means that there is intervention of other values which are more dominant to influence society's daily attitude. Those other values tend to eliminate society's original values. This research uses qualitative approach with descrptive model. It employs the theory of subject by Slavoj Zizek. This theory point out that subject grows and develops in the daily awareness of society. The result of this research shows that subject emerges in local values which are represented as manifestation of corn rice as embeddedness. There is embeddedness whice can unite society in their daily attitude based on attitude norms in their knowledge. Further more, Giant Tempeh Festival is also process of learning about atificial thing. It means festival is a sign of image of something with material sense which slowly interferes and eliminates the local awareness on local knowledge. Finally the subject begins to move to something which is so artificial.